Implikasi kehadiran desa Dinas Terhadap Pranata ada di Bali (Desa Adat Kesiman, Denpasar Timur, Kota Madya Denpasar = The Implication of Existence of The Desa Dinas on The Traditional Institution Bali - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRAK This research is aimed to understand the power and function of desa adat (village customary law) in maintaining their existence as Balinese traditional social organization, and also to attain some knowledge about the solution to the conflicts, which even strongly attack as well as guard to remain harmony. The selection of Kesiman traditional village as a research object, because of the transitional process of that village in order to express the social cultural phenomena behind the harmony. The theoretical framework for this research is structural-functionalism of B. Malinowski and Radcliffe-Brown, which points out that the total of culture possesses a certain function. Besides that, the conflict theory of L. A. Coser and G. Simmel is also used in this research. The conflict, they clarify, does not exist only in a negative dimension rather it has a positive dimension too because of its ability to integrate the society. Participant observation, in-depth interview are applied as the data collection method for this research. As the findings of this research